Predictors of mortality and ICD shock therapy in primary prophylactic ICD patients-A systematic review and meta-analysis. - Leonard Bergau; Tobias Tichelbäcker; Barbora Kessel; Lars Lüthje; Thomas H Fischer; Tim Friede; Markus Zabel (PLoS ONE)
Background There is evidence that the benefit of a primary prophylactic ICD therapy is not equal in all patients. Purpose To evaluate risk factors of appropriate shocks and all- cause mortality in patients with a primary prophylactic ICD regarding contemporary studies. Data source PubMed, LIVIVO, Cochrane CENTRAL between 2010 and 2016. Study selection Studies were eligible if at least one of the endpoints of interest were reported. Data extraction All abstracts were independently reviewed by at least two authors. The full text of all selected studies was then analysed in detail. Data synthesis Our search strategy retrieved 608 abstracts. After exclusion of unsuitable studies, 36 papers with a total patient number of 47282 were included in our analysis. All-cause mortality was significantly associated with increasing age (HR 1.41, CI 1.29-1.53), left ventricular function (LVEF; HR 1.21, CI 1.14-1.29), ischemic cardiomyopathy (ICM; HR 1.37, CI 1.14-1.66) and co-morbidities such as impaired renal function (HR 2.30, CI 1.97-2.69). Although, younger age (HR 0.96, CI 0.85-1.09), impaired LVEF (HR 1.26, CI 0.89-1.78) and ischemic cardiomyopathy (HR 2.22, CI 0.83-5.93) were associated with a higher risk of appropriate shocks, none of these factors reached statistical significance. Limitations Individual patient data were not available for most studies. Conclusion In this meta-analysis of contemporary clinical studies, all-cause mortality is predicted by a variety of clinical characteristics including LVEF. On the other hand, the risk of appropriate shocks might be associated with impaired LVEF and ischemic cardiomyopathy. Further prospective studies are required to verify risk factors for appropriate shocks other than LVEF to help select appropriate patients for primary prophylactic ICD-therapy.